2008
DOI: 10.1097/ccm.0b013e31818f21aa
|View full text |Cite
|
Sign up to set email alerts
|

Intensive versus conventional insulin therapy: A randomized controlled trial in medical and surgical critically ill patients*

Abstract: Current Controlled Trials registry (ISRCTN07413772) http://www.controlled-trials.com/ISRCTN07413772/07413772; 2005.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
273
3
13

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 418 publications
(297 citation statements)
references
References 23 publications
8
273
3
13
Order By: Relevance
“…Since these studies [446,447] appeared, several RCTs [448][449][450][451][452][453][454][455] and meta-analyses [456][457][458][459][460][461][462] of intensive insulin therapy have been performed. The RCTs studied mixed populations of surgical and medical ICU patients and found that intensive insulin therapy did not significantly decrease mortality, whereas the NICE-SUGAR trial demonstrated an increased mortality [451].…”
Section: We Suggest the Use Of Arterial Blood Rather Than Capillary Bmentioning
confidence: 99%
“…Since these studies [446,447] appeared, several RCTs [448][449][450][451][452][453][454][455] and meta-analyses [456][457][458][459][460][461][462] of intensive insulin therapy have been performed. The RCTs studied mixed populations of surgical and medical ICU patients and found that intensive insulin therapy did not significantly decrease mortality, whereas the NICE-SUGAR trial demonstrated an increased mortality [451].…”
Section: We Suggest the Use Of Arterial Blood Rather Than Capillary Bmentioning
confidence: 99%
“…Our analysis included 14,495 patients from 27 studies 128, 330, 331, 332, 337, 338, 339, 340, 341, 342, 343, 344, 345, 346, 347, 348, 349, 350, 351, 352, 353, 354, 355, 356, 357, 358, 359. None of the studies were especially prone to bias.…”
Section: Cq14: Blood Glucose Managementmentioning
confidence: 99%
“…Overall, 28 articles were excluded ( Figure 1). We included 26 trials [8][9][10][11][12][13]18,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] in the meta-analysis.…”
Section: Literature Searchmentioning
confidence: 99%